The Influence Of Social Media In Learning English For Hospitality And Tourism Students - Magdalena Kartika Sari Tandy Rerung (Akademi Pariwisata Bunda Mulia, 2021)
Since the beginning of the pandemic, education is challenged with the new method of online learning. With regards with the intervention of technology to the learning field, both students and teachers are able continue the teaching and learning process with several adjustments along the side. Social media can be one of the powerful tool during this process. Information such as text and visual are accessible based on these platforms. Therefore gaps between the what has been known and yet unknown is getting narrower. English as the main language in hospitality industry takes an important role in having an effective communication. From practice to the business world, the authenticity of information is also important. Based on the needs reviewed, the following study is discussing about the influence of social media, especially Facebook and Instagram toward the students language learning. The participants are taken from 63 Hospitality and Industry – Bunda Mulia University students who were taking General English as one of their course subjects. Results shown that most the students agree and extremely agree on how social media influence their language learning in various perspectives. Therefore as conclusions, educators as well teachers are encouraged to support their students in expressing their English whenever they use the social media platforms.